Hybrid Effect And Stacking Sequence On Mechanical And Morphological Properties Of Flax/Glass Fiber Reinforced Epoxy Composites - Mohd Razali, Aisyah Awanis (Universiti Sains Malaysia, 2022)
Hybrid composite laminates have recently become one of the most actively researched materials due to outstanding properties. This research looks at the use of flax and glass fibers which both have a great potential in the field of composite manufacturing. The aim of this research is to investigate the hybrid effects of natural and synthetic fibers as well as the effects of stacking sequence on the mechanical and morphological properties of flax/glass fiber reinforced epoxy composites. The composite laminates were fabricated from untreated flax fiber and no modification to the surface of glass fiber or the matrix. Composite laminates were produced by hand lay-up and then compacted by vacuum bagging. The tensile, flexural, and impact characteristics of six laminates were measured. Results indicate that the mechanical properties of hybrid composites fall between those of non-hybrid FFRE and GFRE composites, which outperformed the control sample (FFRE). Among the hybrid composites developed, sample H2 [GF]s has the best stacking sequence in terms of elastic modulus, bending modulus, and impact toughness (2.07 GPa, 9.78 GPa, and 10.14 kJ/m2, correspondingly). The SEM micrograph of fractured composites reveals failure signs such as fiber breakage, fiber pull out, matrix breakage, debonding, and delamination, which characterize the level of fiber and polymer matrix adhesion. Crisp and clear matrix cracks demonstrate the brittle failure. The collected data could be utilized to create new hybrid laminated composites for industrial applications such as aerospace, automotive, structural and non-structural.